(untitled) (Bangladesh Medical Journal, 2014)
The causes of polyneuropathy are many and it is important to identify them, as some of them, especially the inflammatory types are treatable. To explore the different etiological factors of polyneuropathy, this cross sectional study was carried out in the department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka. Data were collected by taking medical history and clinical examination and subsequent laboratory investigations. A total of 60 subjects were included in this study and mean age of the entire patient was 42.25 year. Out of all respondents, 83.3% had muscle weakness, similar number had problems with object handling, 66.3% had muscle cramp, 63.3% had impaired standing or gait, 55.0% had distal paraesthesia, 41.7% had burning feet, 8.3% had restless legs and 5.0% had stiffness. Out of all patients of polyneuropathy, 33.3% had diabetic neuropathy, 11.7% had Guillain-Barré syndrome, 10.0% had chronic inflammatory demyelinating polyneuropathy, similar number had unknown etiology, 6.7% had charcot-marry-tooth disease disease, 6.7% had renal failure, 5.0% had leprosy, Vitamin B 12 deficiency and chronic liver disease of each, 3.3% had history of isoniazide drug intake and similar had systemic lupus erythromatosus. We conclude that, polyneuropathy has wide variety of etiological factors. Among them, diabetes is the most common factor. Further large controlled study is needed to establish the etiological pattern in the context of Bangladesh. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21371 Bangladesh Med J. 2014 January; 43 (1): 17-20